Diversity of Medicinal Plants and Preliminary Parameterization of their Uses in Benin (Western Africa) - PADONOU, Elie Antoine; KINDOMIHOU, M. VALENTIN; DJEGO, JULIEN GAUDENCE MATHURIN; SINSIN, Brice (My University, 2012)
An investigation was conducted in Benin botanical gardens, endogenous therapeutic gardens and forests in order to assess diversity of medicinal plants and their endogenous, alimentary and medicinal importance. A preliminary parameterization to assess the importance range of these medicinal plants was performed. To that end, three indices were built such as National Identity Coefficient (NIC), National Utility Coefficient (NUC), and Alimentary Utility Index (AUI) per family. Relation between these indices and botanical families was assessed using factorial correspondence analysis. Ailments treated per family and percentage of organ solicited per family, were also assessed. As results, the medicinal plants observed globally belong to 15 botanical families. The NIC ranges from 0.31 to 1, and shows eight families that are mostly identified at national scale. The NUC ranges from 0.26 to 1, and indicates seven mostly useful families, i.e. Apocynaceae, Capparidaceae, Euphorbiaceae, Annonaceae, Meliaceae, Rutaceae and Sterculiaceae; but these are not belonged to the most identified families at the national scale. The AUI ranging from 6 to 50, pointed out eight families i.e. Capparidaceae, Annonaceae, Sterculiaceae, Mimosaceae, Bignoniaceae, Combretaceae, Ceasalpiniaceae and Bombacaceae; these are mostly used as food, with 50% highly solicited in treating more ailments. Polygaceae and Flacourtiaceae are the mostly threatened as 70% of their species roots are solicited for various uses. Further studied are needed to standardize these indices.
Keywords: Medicinal Plants; Family; Parameterization